Micro Hydro Power: A Source of Sustainable Energy in Rural Communities: Economic and Environmental Perspectives (The Pakistan Development Review, 2015)
Energy is an important need of human life. It is the life blood of all economic activities. Due to increase in population and economic activities, the need for energy is increasing at a faster rate. Without having sufficient energy, the goal of economic and social development and the Millennium Development Goals in particular cannot be achieved. Most of the rural areas in different parts of the world are without electricity. About 1.6 billion people in the world who are living in rural areas are without electricity [Greenstone (2014)]. The reason is that it is too costly to provide electricity services to rural communities through conventional means due to remote location and low density of population. Moreover, due to poverty and low income the rural inhabitants are not in a position to afford the main grid electricity. The use of diesel and gasoline has been used for decades for provision of electricity to rural areas. But it was not so successful due to economic, technical and environmental problems [Woodruff (2007a)].